Effect of Steady and Dynamic Blood Pressure Parameters During Thrombectomy According to the Collateral Status. Issue 4 (April 2020) - Maïer, Benjamin; Dargazanli, Cyril; Bourcier, Romain; Kyheng, Maëva; Labreuche, Julien; Mosimann, Pascal J.; Puccinelli, Francesco; Taylor, Guillaume; Le Guen, Morgan; Riem, Romuald; Desilles, Jean-Philippe; Boisseau, William; et al.
Abstract : Background and Purpose—: Guidelines regarding blood pressure (BP) management during endovascular therapy (EVT) for anterior circulation strokes are questionable since the optimal BP target is a matter of debate. To evaluate the importance of hemodynamic control during EVT, we investigated the impact of dynamic and steady BP parameters during EVT on functional outcome (part 1) and according to the collateral status (CS; part 2). Methods—: We performed a post hoc analysis of the ASTER trial (Contact Aspiration Versus Stent Retriever for Successful Recanalization). BP was measured noninvasively during EVT and CS assessed on the angiographic run before EVT. We studied dynamic BP parameter using BP variability (coefficient of variation) and steady BP parameter (hypotension time defined as systolic BP <140 mm Hg and mean arterial pressure <90 mm Hg). The primary outcome was favorable outcome defined as a 3-month modified Rankin Scale score between 0 and 2. Results—: Among the 381 patients of the ASTER study, 172 patients were included in part 1 and 159 in part 2. Systolic BP, diastolic BP, and mean arterial pressure variability were negatively associated with favorable outcome regardless of CS: per 10-unit increase, adjusted odds ratios were 0.45 (95% CI, 0.20–0.98), 0.37 (95% CI, 0.19–0.72), and 0.35 (95% CI, 0.16–0.76), respectively. According to CS, the hypotension time with periprocedural mean arterial pressure <90 mm Hg was negatively associated with favorable outcome in patients with poor CS (adjusted odds ratio, 0.88 [95% CI, 0.72–1.09]) but not in patients with good CS (adjusted odds ratio, 1.24 [95% CI, 0.91–1.67]; P het =0.047). Conclusions—: The CS did not modify the association between dynamic parameters and functional outcomes, but some findings suggest that the CS modifies the association between steady parameter and functional outcomes. Hypotension time according to the CS was not statistically predictive of poor outcomes but displayed a trend toward worse outcomes for patients with poor CS only. Abstract : Supplemental Digital Content is available in the text.